Blockade of endogenous opioid neurotransmission enhances acquisition of conditioned fear in humans. - Eippert, F; Bingel, U; Schoell, E; Yacubian, J; Büchel, C (2008)
The endogenous opioid system is involved in fear learning in rodents, as opioid agonists attenuate and opioid antagonists facilitate the acquisition of conditioned fear. It has been suggested that an opioidergic signal, which is engaged through conditioning and acts inhibitory on unconditioned stimulus input, is the source of these effects. To clarify whether blockade of endogenous opioid neurotransmission enhances acquisition of conditioned fear in humans, and to elucidate the neural underpinnings of such an effect, we used functional magnetic resonance imaging in combination with behavioral recordings and a double-blind pharmacological intervention. All subjects underwent the same classical fear-conditioning paradigm, but subjects in the experimental group received the opioid antagonist naloxone before and during the experiment, in contrast to subjects in the control group, who received saline. Blocking endogenous opioid neurotransmission with naloxone led to more sustained responses to the unconditioned stimulus across trials, evident in both behavioral and blood oxygen level-dependent responses in pain responsive cortical regions. This effect was likely caused by naloxone blocking conditioned responses in a pain-inhibitory circuit involving opioid-rich areas such as the rostral anterior cingulate cortex, amygdala, and periaqueductal gray. Most importantly, naloxone enhanced the acquisition of fear on the behavioral level and changed the activation profile of the amygdala: whereas the control group showed rapidly decaying conditioned responses across trials, the naloxone group showed sustained conditioned responses in the amygdala. Together, these results demonstrate that in humans the endogenous opioid system has an inhibitory role in the acquisition of fear.